Synthesis and characterization of MX2 and exfolation MX2 (M=Mo ,W; X = O, S, Se and Te) and their electrochemical properties - Poh, Yi Fei (2016)
Electrical Energy Storage (EES) refers to a process of converting electrical energy to electrical energy from a power network into a form that can be stored. Development of energy storage devices or related energy conversion is required to harvest the energy effectively. Energy storage is the most promising technology to reduce fuel consumption. So, the energy storage devices can be classified into batteries, capacitors and electrochemical capacitors. Capacitance and charge storage property of a supercapacitor depends on electrode materials used. Electrode materials of supercapacitor could be categorized into three types, viz., activated carbon materials, conducting polymers, and metal oxides (e.g., RuO2, MnO2, MoO2). Transition metal dichalcogenide (TMD) compounds MX2, where M is a transition metal of groups 4–10 and X is a chalcogen from the periodic table.From this research should synthesis transition metal dichalcogenides (MX2) where M = Mo and W, and X = O, S, Se and Te using hydrothermal method, and fabricate MX2 using exfoliation method ,characterize the synthesized MX2, and exfoliated MX2 samples using physico-chemical technique.and to evaluate the electrochemical properties of the MX2 and exfoliated MX2 using potentiostat-galvanostat. The material are characterized by X-ray diffraction (XRD),Field Emission Scanning Electron Microscopy (FESEM) and the nanomaterial was coated on electrode to carry out electrochemical testing like cyclic voltammetry (CV), galvanostatic charge-discharge cycle (CDC) and Electrochemical impedance spectroscopy (EIS). The XRD result shows that the material is formed because all the diffraction peaks of material are present in it. The morphology of layer structure found in MoO3, exfoliated MoO3, MoSe2 and exfoliated MoSe2 electrodes. Agglomeration structure found in MoS2 and exfoliated MoS2. The specific capacitance of exfoliated material also is higher than the bulk material, for example specific capacitance of exfoliated MoO3 is 16.1 F/g is higher than bulk MoO3 that is 9 F/g. Specific capacitance of exfoliated MoS2 is 260 F/g is higher than bulk MoS2 that is 95.1 F/g. Specific capacitance of exfoliated MoSe2 is 8.0 F/g is higher than bulk MoSe2 that is 5.7 F/g.This shows a superior performance of exfoliated material than the bulk component material. The exfoliated material shows a higher Cs as compared with bulk component material at 0.3 A/g. Exfoliated material shows higher ES and PS than the bulk material. For EIS result, resistance of exfoliated material is lower the bulk material generally.